Compound Danshen Dripping Pill Inhibits Retina Cell Apoptosis in Diabetic Rats - Zhang, Qian; Xiao, Xinhua; Zheng, Jia; Li, Ming; Yu, Miao; Ping, Fan; Wang, Tong; Wang, Xiaojing (Frontiers in Physiology, 2018)
Scope: Diabetic retinopathy (DR) is a severe microvascular complication of diabetes. Previous clinical trials have shown that Compound Danshen Dripping Pill (CDDP) improves DR symptoms. However, the mechanism involved remains unclear. Procedures: Rats fed a high-fat diet and injected with streptozotocin (STZ) were used as an experimental type 2 diabetes rodent model. CDDP was administered to two groups of diabetic rats at 0.2 g/kg/day and 0.4 g/kg/day via gastric gavage for 12 weeks. After the 12 weeks of treatment, retinal function was evaluated by electroretinography (ERG). Histological staining and TdT-mediated dUTP nick-end labeling (TUNEL) assays were also performed. Retinal genome expression was determined by gene array. Results: We found that CDDP moderated ERG and histological abnormalities in diabetic rats, independent of blood glucose level. A gene array showed that CDDP changed 262 genes significantly in the diabetic retina. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated that differentially expressed genes in the CDDP-treated groups were involved mainly in the apoptosis pathway. Moreover, CDDP reduced the number of TUNEL-positive cells in the diabetic retinas. CDDP prevented the reduction in Bcl-2 expression and the increase in BCL-2 associated X (Bax) and caspase-3 (Casp3) expression in diabetic rats. Conclusion: Our results suggest that CDDP exerts its neuroprotective functions by inhibiting cell apoptosis in diabetic rats.